Using symbolic computation in the characterization of frictional instabilities involving orthotropic materials - Agwa, Mohamed A.; Pinto da Costa, António (Zielona Góra: Uniwersytet Zielonogórski)
The present work addresses the problem of determining under what conditions the impending slip state or the steady sliding of a linear elastic "orthotropic" layer or half space with respect to a rigid flat obstacle is dynamically unstable. In other words, we search the conditions for the occurrence of smooth exponentially growing dynamic solutions with perturbed initial conditions arbitrarily close to the steady sliding state, taking the system away from the equilibrium state or the steady sliding state.
Keywords: Coulomb friction; dynamic instabilities; surface solutions; orthotropic material